Pengembangan desain becak listrik sebagai upaya pelestarian transportasi becak di kota Yogyakarta - Laurensius Windy Octanio Haryanto; Imam Damar Djati; Dwinita Larasati (Fakultas Seni Rupa dan Desain ITB, 2020)
Yogyakarta city in the era of globalization has been developing without losing its historical and cultural values, which are owned as regional identity. This identity makes Yogyakarta city has a tourist attraction value both for domestic and international tourists. Electric pedicab is one of alternative transportations in Yogyakarta that is able to support tourism activities. In the development of city transportation, electric pedicab is the result of the transformation of traditional pedicab, one of the cultural heritages in Yogyakarta. The purpose of transformation effort is to preserve pedicab transportation and to respond issues related to sustainability threat. Design has also become one of the aspects that needs to be considered in developing pedicab transportation. This study reviews and analyzes various factors that can influence the design of an electric pedicab, so that it can be a reference in further design development. This research use qualitative approach and supported by observation and purposive sampling interviews. The result of this study is a new electric pedicab design concept, without losing the design characteristics of the traditional Yogyakarta pedicab.Keywords: electric pedicab, transportation, tourism, Yogyakarta